The Analysis Study of Diagnosis and Management of Giant Omphaloceles: A Comprehensive Systematic Review - Risko Sandy; I Gusti Agung Ngurah Maha Yudha; I Made Darmajaya (International Medical Journal Corp. Ltd, 2024)
Background: Giant omphalocele (GO) is a severe form of omphalocele, characterized by a defect larger than 5 cm, often including the liver. Management strategies include staged surgical closure and non-operative delayed closure, with the latter focusing on neo-epithelialization and secondary operations. This study aims to explore diagnosis and management during neonatal care. Methods: This systematic review exclusively examined full-text articles published in English between 2014 and 2024, adhering to the PRISMA 2020 guidelines. Result: The study conducted a thorough review of more than 300 publications that were obtained from reputable databases, such as ScienceDirect, SagePub, and PubMed. Eight publications were identified as necessitating a more comprehensive examination subsequent to an initial screening. As a result, a comprehensive review of these selected studies was conducted to guarantee an exhaustive and rigorous assessment. Conclusion: Giant omphaloceles management involves a multifaceted approach, including primary closure, staged surgical closure, and nonoperative delayed closure. Synthetic materials and biological meshes promote granulation tissue formation and gradual closure, but further research is needed to reduce morbidity and mortality.